Literasi Matematika sebagai Kompetensi Utama di Abad 21 dan Implikasinya pada Pendidikan di Sekolah Dasar - Laila Hafani Rambe; Lasmida Malau; Meifa Efata Rey Manurung; Neysa Afifah Lubis; Wulan Kurnia Denti (Indonesian Journal Publisher, 2023)
Students will not master mathematics material if they have difficulty in understanding concepts. To understand concepts, literacy skills are needed. Someone who can understand concepts well and is also skilled in mathematics should be sensitive to mathematical concepts related to problems. From this awareness then comes the strategy to formulate the problem in mathematical form and then solve it. Formulating, applying and interpreting are all part of this process. The purpose of this research is to explore the concept of mathematical literacy and analyse the role of mathematical literacy in the 21st century, examining some of the factors that are thought to influence mathematical literacy achievement and mathematical connection skills. The results showed that mathematical literacy can be realised through contextualised learning in achieving the goal of mathematical literacy, teachers must engage students in important activities that help them relate academic lessons to the real-world contexts they face. Mathematical literacy can be realised in learning that is concrete and teachers should teach by linking learning with students’ daily lives by doing contextual learning or doing the Realistic Mathematics Learning movement, both of which are considered good in improving the mathematical literacy skills of elementary school student.